TREES AND REGENERATION IN RUBBER AGROFORESTS AND OTHER FOREST-DERIVED VEGETATION IN JAMBI (SUMATRA, INDONESIA) - Hesti L. Tata; Meine van Noordwijk; Marinus Werger (Indonesian Journal of Forestry Research, 2008)
The rubber  agroforests  (RAF)  of Indonesia provide  a dynamic interface  between natural  processes  of forest  regeneration and  human’s management   targeting  the harvesting  of latex  with  minimum investment  of time  and financial  resources.  The composition  and species richness  of higher  plants  across an intensification gradient from forest to monocultures of tree crops have been investigated  in six land use types (viz. secondary forest, RAF, rubber monoculture, oil palm plantation, cassava field and Imperata grassland)  in Bungo,  Jambi  Province,  Indonesia.  We emphasize  comparison of four different  strata  (understory, seedling,  sapling  and tree) of vegetation  between forest and RAF,  with  specific interest  in plant  dependence  on ectomycorrhiza fungi. Species richness  and species accumulation curves for seedling  and sapling  stages were similar  between forest and RAF,  but in the tree stratum  (trees > 10 cm dbh) selective thinning by farmers was evident in a reduction  of species diversity and an increase in the proportion of trees with edible parts. Very few trees dependent on ectomycorrhiza fungi were encountered  in the RAF. However, the relative distribution of early and late successional species as evident from the wood density distribution showed no difference between RAF and forest.